Pengaruh Struktur Modal, Likuiditas, dan Perputaran Aktiva terhadap Profitabilitas Pada Perusahaan Sektor Energi yang Terdaftar di BEI Periode 2019-2023 - Lutfi Asiah Azhari; Sudradjat Sudradjat; Arwan Gunawan; Hastuti Hastuti (Indonesian Accounting Literacy Journal, 2026)
Abstract: This study aims to determine the effect of capital structure, liquidity, and asset turnover on profitability. The independent variables in this study is the capital structure measured using the Debt to Assets Ratio (DAR); liquidity measured by Current Ratio (CR); and asset turnover as measured by Total Assets Turnover (TATO). The dependent variable used is profitability as measured by Return on Assets (ROA). The sample of this research is energy sector companies listed on the Indonesia Stock Exchange in 2019-2023 (5 years) using purposive sampling techniques. This research uses a quantitative method. The data used in this research are secondary data obtained from financial statements and annual reports published by the Indonesia Stock Exchange (www.idx.co.id) and the company's website. The analysis and hypothesis testing technique uses panel data regression analysis. The results showed that capital structure and assets turnover had a significant effect on profitability, while liquidity showed the opposite. While simultaneously, capital structure, liquidity, and asset turnover affect profitability.